FLOCK IMMUNITY AGAINST MAREK’S DISEASE - Jayalakshmi, K; Selvaraju, G; Dinakaran, A Manicavasaka; Gopalakrishnamurthy, T R; Geetha, M; Saravanan, S (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The flock immunity against Marek’s disease in commercial layer flocks was assessed by Quantitative agargel immunodiffusion (QAGID) test. The mean QAGID titre ranges from zero to 3.7 and 10.4 to 22.4 in outbreaks and convalescent birds respectively. Dose, type and time of Marek’s disease vaccination influence the quantum of humoral immune response during outbreak. Though the level of antibodies against Marek’s disease virus (MDV) are not directly related with disease resistance, quantification of MDV antibodies is a useful tool in determining Herpes virus of turkey (HVT) viraemia, which is necessary for the induction of immunity.